2015
DOI: 10.1007/s11030-015-9569-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and protein engineering studies of active and inactive states of human dopamine D2 receptor (D2R) and investigation of drug/receptor interactions

Abstract: Homology model structures of the dopamine D2 receptor (D2R) were generated starting from the active and inactive states of β2-adrenergic crystal structure templates. To the best of our knowledge, the active conformation of D2R was modeled for the first time in this study. The homology models are built and refined using MODELLER and ROSETTA programs. Top-ranked models have been validated with ligand docking simulations and in silico Alanine-scanning mutagenesis studies. The derived extra-cellular loop region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…Furthermore, by applying Ballesteros & Weinstein numbering (B&W) [42] the position of considered important residues was more easily comparable between all receptors. Mutagenesis studies have shown that for dopamine binding, the endogenous agonist of the DR, a negatively charged aspartate (3.32Asp) is believed to form a ionic bond interaction with the protonable amine of dopamine [2,41,43]. Moreover, it was shown that this effect was crucial for ligand binding and that this amino acid was not only conserved among the DR, but also in all biogenic amine GPCRs [44,45].…”
Section: Ligand Binding To Dopamine Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by applying Ballesteros & Weinstein numbering (B&W) [42] the position of considered important residues was more easily comparable between all receptors. Mutagenesis studies have shown that for dopamine binding, the endogenous agonist of the DR, a negatively charged aspartate (3.32Asp) is believed to form a ionic bond interaction with the protonable amine of dopamine [2,41,43]. Moreover, it was shown that this effect was crucial for ligand binding and that this amino acid was not only conserved among the DR, but also in all biogenic amine GPCRs [44,45].…”
Section: Ligand Binding To Dopamine Receptorsmentioning
confidence: 99%
“…Moreover, it was shown that this effect was crucial for ligand binding and that this amino acid was not only conserved among the DR, but also in all biogenic amine GPCRs [44,45]. Also, a serine microdomain on TM5 (5.42Ser, 5.43Ser, 5.46Ser) was considered as an important feature for dopaminergic binding in all DRs as it is believed that the serines form hydrogenic bonds with the catechol hydroxyls of dopamine, increasing the binding affinity and orienting ligands in the orthosteric binding pocket [38,43,[46][47][48]. While 5.42Ser seems to be critical, 5.43Ser plays a less important role [38].…”
Section: Ligand Binding To Dopamine Receptorsmentioning
confidence: 99%
“…A combination of MODELLER (Eswar et al, 2007) and the ROSETTA loop-modeling protocol (Das & Baker, 2008) was performed to build and refine the 3D structure of D2R. The details of the modeling process were explained in our previous work (Salmas et al, 2015).…”
Section: Homology Modelingmentioning
confidence: 99%
“…In the current study, we refine the small molecule binding poses derived from docking and molecular dynamics (MD) trajectory frames in order to obtain an accurate ligand binding energy to the D2R models obtained in our earlier studies (Durdagi, Salmas, Stein, Yurtsever, & Seeman, 2016;Salmas, Yurtsever, Stein, & Durdagi, 2015;Salmas et al, 2017aSalmas et al, , 2017b. The D2R state models were generated by the use of comparative modeling approaches based on the inactive beta-2 adrenergic receptor (β 2 adrenoreceptor) as a template structure (Hanson et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation